(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
According to the World Health Organization (WHO), more than 1 billion people have various forms of disability, which is almost 15% of the world’s population. Wars, infectious diseases, hereditary diseases, environmental disasters, crime, alcoholism, drug addiction, accidents, birth defects and injuries contribute to the increase in the number of people with disabilities - about 23 thousand per day, which is more than 8 million people per year. Such a significant number of people with disabilities requires civilized society to develop effective social protection measures and reintegrate these people into full-fledged social life. In this process, the development of new ways of acting and learning social experience, which is the result of the activity of consciousness, plays a major role. Adaptive physical culture is a relatively new area in the Ukrainian system of education and science, and therefore its terminology, functions, tasks and results are still under development. The article summarizes scientific approaches to adaptive physical culture, creates a unified system that allows structuring its essential features, types, tasks and expected results, and offers a comprehensive definition of this concept. After presenting the system of adaptive physical culture, its content is considered with regard to the modern specifics of consciousness and behavior of mankind. The specificity of modern consciousness is that scientific and technological progress has created the illusion of humanity’s relative independence from natural laws, which has led to a move away from a healthy lifestyle. Among all the cited researchers, only three paid attention to a healthy lifestyle as a separate concept, and not only to its components that are traditionally included in physical education. The article also examines the components and structure of a healthy lifestyle, revealing that it is inherently not inferior to other aspects of adaptive physical education, so it can be included as a full-fledged component of this discipline. At the same time, it is noted which aspect is traditionally ignored within the framework of a healthy lifestyle. Since a healthy lifestyle is a relatively new area of science, its concept is not sufficiently developed even for healthy individuals, and it has specific requirements for people with disabilities.